An apple MYB transcription factor regulates cold tolerance and anthocyanin accumulation and undergoes MIEL1‐mediated degradation. Issue 2 (10th July 2019) - An, Jian‐Ping; Wang, Xiao‐Fei; Zhang, Xiao‐Wei; Xu, Hai‐Feng; Bi, Si‐Qi; You, Chun‐Xiang; Hao, Yu‐Jin
Summary: MYB transcription factors (TFs) have been demonstrated to play diverse roles in plant growth and development through interaction with basic helix‐loop‐helix (bHLH) TFs. MdbHLH33, an apple bHLH TF, has been identified as a positive regulator in cold tolerance and anthocyanin accumulation by activating the expressions of MdCBF2 and MdDFR . In the present study, a MYB TF MdMYB308L was found to also positively regulate cold tolerance and anthocyanin accumulation in apple. We found that MdMYB308L interacted with MdbHLH33 and enhanced its binding to the promoters of MdCBF2 and MdDFR . In addition, an apple RING E3 ubiquitin ligase MYB30‐INTERACTING E3 LIGASE 1 (MdMIEL1) was identified to be an MdMYB308L‐interacting protein and promoted the ubiquitination degradation of MdMYB308L, thus negatively regulated cold tolerance and anthocyanin accumulation in apple. These results suggest that MdMYB308L acts as a positive regulator in cold tolerance and anthocyanin accumulation in apple by interacting with MdbHLH33 and undergoes MdMIEL1‐mediated protein degradation. The dynamic change in MYB‐bHLH protein complex seems to play a key role in the regulation of plant growth and development.